Genetic variants in genes involved in creatine biosynthesis in patients with severe obesity or anorexia nervosa - Rajcsanyi, Luisa S.; Hoffmann, Anne; Ghosh, Adhideb; Matrisch-Dinkler, Birgit; Zheng, Yiran; Peters, Triinu; Sun, Wenfei; Dong, Hua; Noé, Falko; Wolfrum, Christian; Herpertz-Dahlmann, Beate; Seitz, Jochen; et al. (Frontiers in Genetics, 2023)
Increased thermogenesis in brown adipose tissue might have an obesity-reducing effect in humans. In transgenic mice, depletion of genes involved in creatine metabolism results in disrupted thermogenic capacity and altered effects of high-fat feeding on body weight. Analyses of a large meta-analysis of a sex-stratified genome-wide association study (GWAS) for body mass index (BMI) within the genomic regions of genes of this pathway (CKB, CKMT1B, and GATM) revealed one sex-dimorphic BMI-associated SNP in CKB (rs1136165). The effect size was larger in females than in males. A mutation screen of the coding regions of these three candidate genes in a screening group (192 children and adolescents with severe obesity, 192 female patients with anorexia nervosa, and 192 healthy-lean controls) identified five variants in each, CKB and GATM, and nine variants in the coding sequence of CKMT1B. Non-synonymous variants identified in CKB and CKMT1B were genotyped in an independent confirmation study group (781 families with severe obesity (trios), 320 children and adolescents with severe obesity, and 253 healthy-lean controls). In silico tools predicted mainly benign yet protein-destabilizing potentials. A transmission disequilibrium test in trios with severe obesity indicated an obesity-protective effect of the infrequent allele at rs149544188 located in CKMT1B. Subsequent correlation analyses in 1,479 individuals of the Leipzig Obesity BioBank revealed distinct correlations of CKB with the other two genes in omental visceral adipose tissue (VAT) and abdominal subcutaneous adipose tissue (SAT). Furthermore, between-subject comparisons of gene expression levels showed generally higher expressions of all three genes of interest in VAT than in SAT. Future in vitro analyses are needed to assess the functional implications of these findings.